1970
DOI: 10.3329/jcmcta.v19i2.3871
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid disorders in female subfertility

Abstract: Key words: thyroid dysfunction; female subfertilitydoi: 10.3329/jcmcta.v19i2.3871Journal of Chittagong Medical College Teachers' Association 2008: 19(2):46-50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
4
16
1
Order By: Relevance
“…Sharma et al 24 in their study in India reported hypothyroidism in 20% and hyperthyroidism in 3% of primary infertile women. Similarly, a study done in 2007 in Bangladesh by Rahaman et al 20 showed hypothyroidism in 33.3% of infertile women and hyperthyroidism in none. Goswani et al 25 performed a study in Delhi in 2007 and found hypothyroidism in 8% infertile women and hyperthyroidism in 5%.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Sharma et al 24 in their study in India reported hypothyroidism in 20% and hyperthyroidism in 3% of primary infertile women. Similarly, a study done in 2007 in Bangladesh by Rahaman et al 20 showed hypothyroidism in 33.3% of infertile women and hyperthyroidism in none. Goswani et al 25 performed a study in Delhi in 2007 and found hypothyroidism in 8% infertile women and hyperthyroidism in 5%.…”
Section: Discussionmentioning
confidence: 81%
“…This high prevalence could be because infertile women having tubular endometriosis on diagnostic laparoscopy or hysteroscopy, with genital TB (PCR-positive), with liver, renal or cardiac diseases, those already on treatment for thyroid disorders or hyperprolactinemia or cases where abnormality was found in husband's semen analysis also were excluded from their study. Likewise, Rahaman et al 20 conducted a case control study in 30 infertile women and 30 fertile women in 2007 in Bangladesh excluding the women with organic lesion in uterus or ovary and with history of previous abdominal surgery. They reported the prevalence of thyroid disorder as 33.3% which was higher than the present study.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Binita et al found the prevalence to be 8% while Sharma et al found the prevalence to be 20%. 6,10 The prevalence of thyroid dysfunction in infertile women was found to be 33.3% in a study by Rahman et al and 23% by Sharma et al 11,12 In this study, thyroid dysfunction was present in 25.5% of the infertile women, where 23.5% had hypothyroidism and 2% had hyperthyroidism. It is obvious from the observation that fertility of female reproductive system is hampered by altered thyroid hormone levels.…”
Section: Discussionmentioning
confidence: 52%
“…7 Hyperprolactinemia which results from a longstanding primary hypothyroidism may result in ovulatory dysfunctions ranging from inadequate corpus luteal progesterone secretion to oligomenorrhoea or ammenorhoea. 11 Amenorrhoea occurs in hypothyroidism due to hyperprolactinaemia, which results from a defect in the positive feedback of oestrogen on LH, and because of the suppression of LH and FSH. 12 Thyroid dysfunction is implicated in a broad spectrum of reproductive disorders, ranging from abnormal sexual development to menstrual irregularities and infertility.…”
Section: Introductionmentioning
confidence: 99%
“…3 It is anticipated that globally 60-80 million couples face the problem to conceive every year. 4 The prevalence of infertility in Pakistan has been estimated which is about 21.9%. 5 WHO (World Health Organization) has defined subfertility clinically as "Inability of a couple to achieve a pregnancy after 12 months (under 35 year of age) or within 6 months (above 35 year of age) of regular unprotected sexual intercourse".…”
Section: Introductionmentioning
confidence: 99%